The clinical significance of intraoperative lavage fluid culture during pancreaticoduodenectomy on organ/space surgical site infection - Yifei Yang; Jianjie Sheng; Chenglin Lu; Hao Cheng; Gang Li; Liang Mao; Chuang Chen; Yudong Qiu; Chang Liu; Xu Fu (Scientific Reports)
Abstract Organ/space surgical site infection (SSI) are common after pancreaticoduodenectomy (PD). There is limited research on the clinical impact of intraoperative lavage fluid contamination in patients undergoing PD. One hundred five patients who underwent PD between August 2022 and July 2023 were retrospectively enrolled. The intraoperative bile and peritoneal lavage were collected for bacterial culture. Postoperative drainage bacterial cultures were performed every 2–3 days thereafter until drains were all removed. The bacteria isolated from intraoperative lavage fluid, intraoperative bile, and postoperative drainage fluid were examined in detail. The risk factors associated with positive intraoperative lavage fluid culture were analyzed through both univariate and multivariate analyses. Organ/space SSI occurred in 59(56.2%) of the 105 patients. The positivity rates of cultures in intraoperative lavage fluid, intraoperative bile, and postoperative drainage fluid were found to be 41.0%, 67.6%, and 84.8%, respectively. Patients with positive intraoperative lavage fluid culture had a significantly higher occurrence of organ/space SSI compared to the negative group (69.0% vs. 29.4%, P < 0.001). Preoperative biliary drainage (PBD) was identified as the only independent risk factor for the contamination of intraoperative lavage fluid (OR = 7.687, 95% CI: 2.164–27.300, P = 0.002). K. pneumoniae was the most common isolates both in the intraoperative lavage fluid and postoperative drainage fluid. Intraoperative lavage fluid contamination closely correlated with organ/space SSI after PD. Meanwhile, PBD was the only risk factor for the contamination of intraoperative lavage fluid.